Virtual reality-based therapy for the treatment of balance deficits in patients receiving inpatient rehabilitation for traumatic brain injury. (February 2014) - Cuthbert, Jeffrey P.; Staniszewski, Kristi; Hays, Kaitlin; Gerber, Don; Natale, Audrey; O'Dell, Denise
Abstract Objective: To evaluate the feasibility and safety of utilizing a commercially available virtual reality gaming system as a treatment intervention for balance training. Design: A randomized controlled trial in which assessment and analysis were blinded. Setting: An inpatient rehabilitation facility. Intervention: Interventions included balance-based physical therapy using a Nintendo Wii, as monitored by a physical therapist, and receipt of one-on-one balance-based physical therapy using standard physical therapy modalities available for use in the therapy gym. Results: Participants in the standard physical therapy group were found to have slightly higher enjoyment at mid-intervention, while those receiving the virtual reality-based balance intervention were found to have higher enjoyment at study completion. Both groups demonstrated improved static and dynamic balance over the course of the study, with no significant differences between groups. Correlational analyses suggest a relationship exists between Wii balance board game scores and BBS scores for measures taken beyond the baseline assessment. Conclusions: This study provides a modest level of evidence to support using commercially available VR gaming systems for the treatment of balance deficits in patients with a primary diagnosis of TBI receiving inpatient rehabilitation. Additional research of these types of interventions for the treatment of balance deficits is warranted.